A protégé semantic modelling approach for combination correlation of manufacturing service. (2017) - Xiang, Feng; Liu, Jiangchun; Jiang, Guozhang; Chen, Xiaowu
Cloud manufacturing service model aimed at gathering global resources, optimise the allocation, provide new impetus for the core of manufacturing industry informatisation and the reform, and the service combination technology is a key technology to optimal allocate various resources in manufacturing cloud. However, because the multiple user demands the high system scalability and task complexity, the potential constraint relationship between the various combinations must be taken into account. Focus on the combinable relations researches on combinable relation classification by workflow and strength degree, such as sequential relationships branch/selection relationships, concurrent relationships, multiple selection, synchronous convergence, discriminator, arbitrary cycle, and delay selection. Finally, we use OWL language to build a model of relations ontology for magnetic bearing.